Efektivitas Penerapan Model Project Based Learning Berbantuan Presentation Intelligence terhadap Peningkatan Kualitas Hasil Proyek Mahasiswa - Cep Miftah Khoerudin (Fakultas Tarbiyah dan Kegurusn Universitas Islam Bandung, 2025)
This study aims to analyze the effectiveness of implementing a Project-Based Learning (PjBL) model enhanced with artificial intelligence (AI) technology in improving the quality of student project outcomes in the Introduction to Social Science course within the Civic Education Study Program. This research adopts a quasi-experimental method with a pretest–posttest control group design involving 40 students divided into experimental and control groups. The analysis results indicate a significant improvement in the experimental group compared to the control group in terms of critical thinking skills, creativity, and the effectiveness of project presentation. These findings demonstrate that integrating the PjBL model with AI technology can enrich project-based learning processes in higher education. Scientifically, the study contributes to strengthening the 21st-century learning paradigm, which emphasizes the synergy between active pedagogy and artificial intelligence innovation.